When a Circle Becomes the Letter O: Young Children’s Conceptualization of Learning and Its Relation With Theory of Mind Development - Wang, Zhenlin; Frye, Douglas A. (Frontiers in Psychology, 2021)
In two independent yet complementary studies, the current research explored the developmental changes of young children’s conceptualization of learning, focusing the role of knowledge change and learning intention, and its association with their developing theory of mind (ToM) ability. In study 1, 75 children from 4- to 6-years of age (Mage = 65.45, SD = 11.45, 36 girls) judged whether a character with or without a genuine knowledge change had learned. The results found that young children over-attributed learning to accidental coincidences that did not involve mental state change. Children’s learning judgments in familiar contexts improved with age, and correlated with their false belief understanding. However, the correlation was no longer significant once age was controlled. Another sample of 72 children between 40 months to 90 months (Mage = 66.87, SD = 11.83, 31 girls) participated in Study 2, where children were asked to judge whether the protagonists in the stories intended to learn and whether they eventually learned. The results suggested that children over-attributed learning intention to discovery learning and implicit learning. They also had trouble with learning scenarios that presented a conflict between the learning intention and outcome. Children’s intention judgment was correlated with their false belief understanding, but the correlation was no longer significant when age was controlled. The implication of the findings for school readiness was discussed. Future research should adopt longitudinal designs to better understand the relation between ToM development and children’s learning understanding.